Some Cyclization Reactions of 6-Mercaptopurine with Expected Biological Activity - HASSAN, A.Y. (Asian Journal of Chemistry, 2024)
The reaction of 6-mercaptopurine 1 with aromatic ketones 2a-h using the acidified acetic acid method afforded the S-acetyl derivatives 3a-h in good yields. While, the cyclized product 4i was obtained directly upon reaction of 1 with 9-acetyl anthracene. Compounds 3a-h were cyclized directly to the corresponding 1,4-thiazino[2,3,4-bc]purine derivatives (4a-h). In the same manner the reaction of 1 with aliphatic, aromatic, alicyclic ketones, α-tetralone and 1-methyl-4-piperidone gave compounds 6, 7, 8, 9a,b, 11 and 12. The cyclized compounds 10a,b were obtained by cyclization of 9a,b. The synthesized compounds were screened for their in vitro antitumor activity at National Cancer Institute.